2016
DOI: 10.1096/fj.201600431r
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury is reduced by the α7nAChR agonist PNU‐282987 through changes in the macrophage profile

Abstract: Nicotinic α-7 acetylcholine receptor (nAChRα7) is a critical regulator of cholinergic anti-inflammatory actions in several diseases, including acute respiratory distress syndrome (ARDS). Given the potential importance of α7nAChR as a therapeutic target, we evaluated whether PNU-282987, an α7nAChR agonist, is effective in protecting the lung against inflammation. We performed intratracheal instillation of LPS to generate acute lung injury (ALI) in C57BL/6 mice. PNU-282987 treatment, either before or after ALI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 63 publications
(112 reference statements)
6
69
1
Order By: Relevance
“…Recently, loss of α7nAChR signal transduction was shown to decrease expression of the canonical M2 marker Arginase-1(52). In addition, use of an α7nAchR agonist decreased the LPS-induced inflammatory response and reversed the inflammatory profile, particularly regarding M1 and M2 polarization, while also improving lung function and remodeling in a model of acute lung injury (15). Based on these findings and those in the current study, we hypothesize that ACh produced by cholinergic lymphocytes acts on macrophages to decrease pro-inflammatory cytokine release and initiate tissue repair during the recovery phase of respiratory viral infection.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Recently, loss of α7nAChR signal transduction was shown to decrease expression of the canonical M2 marker Arginase-1(52). In addition, use of an α7nAchR agonist decreased the LPS-induced inflammatory response and reversed the inflammatory profile, particularly regarding M1 and M2 polarization, while also improving lung function and remodeling in a model of acute lung injury (15). Based on these findings and those in the current study, we hypothesize that ACh produced by cholinergic lymphocytes acts on macrophages to decrease pro-inflammatory cytokine release and initiate tissue repair during the recovery phase of respiratory viral infection.…”
Section: Discussionsupporting
confidence: 72%
“…LPS, E. coli), where injury is increased when cholinergic signaling is inhibited and decreased when it is augmented (15,42,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholinergic agonists can also affect microglial activation and improve cognitive outcomes after trauma and common perioperative complications, such as infection or stroke [31, 32]. Although pharmacological agonists attenuate inflammation in several disease models, they exert off-target effects in other organs, which likely affect multiple physiologic processes ranging from gastrointestinal motility to wound healing [29, 3335]. VNS holds promise also for a more localized response and better patient-specific therapeutic outcomes with fewer side effects, especially through the implementation of targeted and minimally invasive approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the activation of pulmonary macrophages played a critical role in the initiation and development of ALI/ARDS [8]. Recent studies suggested that reprograming macrophages toward M2 phenotype may be an effective strategy to treat ALI/ARDS and other inflammatory diseases [38,39]. Our previous study showed that P12 intervention increased the number of regulatory T (Treg) cells in the lung and draining lymph nodes of ALI mice [24].…”
Section: Effects Of P12 On the Polarization Of Bmdmsmentioning
confidence: 99%